2019
DOI: 10.13189/ujp.2019.070101
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Challenges of Cooperative Learning in Selected College of Arsi University: As a Motivational Factor on Enhancing Students' Learning

Abstract: The objective of this study was to examine the practices and challenges of cooperative learning as a motivational factor on enhancing students' learning in selected colleges of Arsi University. This research has mixed approach both qualitative and quantitative; while its method is descriptive and explorative in their nature. The total sample of the study was 421, 330 graduate students, 85 instructors and the 8 deans and vice deans were included as a sample through stratified random sampling technique. Instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Cooperative learning pedagogy promotes positive interdependence, promotive interaction and individual accountability because the success of one student is dependent on the success of the other students (Johnson et al, 2008). Moges (2019) argued that cooperative learning is an active pedagogical tool that have been found effective in a broad range of subjects because it is often recognised as learner centered, having emerged in opposition to the more traditional methods. This buttresses the role active engagement and interaction plays to enhance students' achievement in the classroom.…”
Section: The Applicability Of Cooperative Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooperative learning pedagogy promotes positive interdependence, promotive interaction and individual accountability because the success of one student is dependent on the success of the other students (Johnson et al, 2008). Moges (2019) argued that cooperative learning is an active pedagogical tool that have been found effective in a broad range of subjects because it is often recognised as learner centered, having emerged in opposition to the more traditional methods. This buttresses the role active engagement and interaction plays to enhance students' achievement in the classroom.…”
Section: The Applicability Of Cooperative Learningmentioning
confidence: 99%
“…This means to say that cooperative learning fashion a new method different from the traditional lecture method because it keeps learners active in the classroom. Moges (2019) also assert that cooperative learning pedagogy is often recognised as learner centered having emerged in opposition to the more traditional methods. It is believed that when cooperative learning is effectively used by teachers or instructors to create an affective learning classroom, it is usually referred to as a learner centered approach (Moges, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Language grooms as a result of interactions done within the society (Zhou & Brown, 2017) as stimulus-response theory (Skinner, 1957) proves that acquisition of a language is a process that directly relates to behavior. In ESL classrooms, teachers act as facilitators (Government of Pakistan, 2006) to make their learners active towards the process of learning (Moges, 2019) and use formative assessment as a means of students' learning. National Curriculum for English is a framework prepared as a reference document that provides guidance and insight to the teachers as stakeholders (Government of Pakistan, 2006).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Gezahegn also stated that the course is more student-centered and communicative than its predecessors. Even though this teaching approach has been applied in schools, problems related to its implementation have been reported (Lucha & Bongase, 2015;Kumar, 2017;Moges, 2019;Reda & Hagos, 2015;Serbessa, 2006;Yayo, 2013). Tirussew, Amare, Jeilu, Tassew, Aklilu, and Berhannu (2018) found that the implementation of CL through the Education Development Army has been found to be poor, contrary to its positive effects on student learning as confirmed by studies from around the world.…”
Section: Introductionmentioning
confidence: 99%